2018
DOI: 10.2214/ajr.17.18323
|View full text |Cite
|
Sign up to set email alerts
|

MRI, Clinical Examination, and Mammography for Preoperative Assessment of Residual Disease and Pathologic Complete Response After Neoadjuvant Chemotherapy for Breast Cancer: ACRIN 6657 Trial

Abstract: Our results indicate that measurement of longest diameter by MRI is more accurate than by mammography and clinical examination for preoperative assessment of tumor residua after NACT and may improve surgical planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(52 citation statements)
references
References 36 publications
(58 reference statements)
3
47
0
2
Order By: Relevance
“…To evaluate residual tumor size, physical examination, mammography, US, and MRI have been used. Of these, MRI is the most accurate method, as it is difficult for other modalities to distinguish posttreatment fibrosis or postbiopsy change from residual tumor following NAC (131,132). However, because findings of breast cancers following NAC vary depending on tumor subtype, histologic type, and time points of MRI acquisitions, a refined strategy for accurate interpretation is crucial.…”
Section: Evaluation Of Women Treated With Neoadjuvant Chemotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate residual tumor size, physical examination, mammography, US, and MRI have been used. Of these, MRI is the most accurate method, as it is difficult for other modalities to distinguish posttreatment fibrosis or postbiopsy change from residual tumor following NAC (131,132). However, because findings of breast cancers following NAC vary depending on tumor subtype, histologic type, and time points of MRI acquisitions, a refined strategy for accurate interpretation is crucial.…”
Section: Evaluation Of Women Treated With Neoadjuvant Chemotherapymentioning
confidence: 99%
“…For the detection of residual cancer after NAC, a meta-analysis including 44 studies (131) found that the median sensitivity was 92% and the median specificity was 90%. Although MRI has a better correlation with pathologic tumor size after NAC than physical examination, mammography, or US (131,132), underestimation or overestimation can occur because of scattered microscopic foci of residual tumor or fibrosis (144). Tumor size evaluation after NAC is therefore somewhat less reliable than that before NAC.…”
Section: Evaluation Of Women Treated With Neoadjuvant Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…For those cases falsely diagnosed as iCR, the residual tumor was generally small [6,18,19]. Volumes of suspicious areas could be acquired preoperatively by MRI prior to pathologic measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical breast exam, mammography, ultrasound, and magnetic resonance imaging (MRI) have been used to evaluate response. Of these, MRI has been found to be the most accurate method, [6][7][8] likely due to its combination of physiologic and morphologic information. A combination of clinical breast exam and imaging may be used to stage the tumor by assigning a category of the extent of disease for the tumor, regional lymph nodes, and distant metastases, as per the American Joint Committee on Cancer 9 (Tables 1-3).…”
Section: Level Of Evidencementioning
confidence: 99%